2021
DOI: 10.1097/sla.0000000000004917
|View full text |Cite
|
Sign up to set email alerts
|

Microaggressions and Implicit Bias in Surgical Training: An Undocumented but Pervasive Phenomenon

Abstract: Objective: To examine the prevalence, nature, and source of microaggressions experienced by surgical residents during training. Summary and Background Data: The role of microaggressions in contributing to workplace culture, individual performance, and professional satisfaction has become an increasingly studied topic across various fields. Little is known about the prevalence and impact of microaggressions during surgical training. Methods: A 46-item survey distributed to current surgical residents in training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 19 publications
4
27
0
Order By: Relevance
“…Microaggressions have previously been reported in surgical specialties. 6,13,14 A 2020 survey completed by 1624 general surgery residents (estimated response rate: 10.2%) and surgical subspecialty residents (estimated response rate: 10.2%) in the United States identified that microaggressions more commonly came from patients, followed by staff, faculty, and coresidents. 13 Only 7% of the trainees reported these events to the graduate medical education office or program director.…”
Section: Discussionmentioning
confidence: 99%
“…Microaggressions have previously been reported in surgical specialties. 6,13,14 A 2020 survey completed by 1624 general surgery residents (estimated response rate: 10.2%) and surgical subspecialty residents (estimated response rate: 10.2%) in the United States identified that microaggressions more commonly came from patients, followed by staff, faculty, and coresidents. 13 Only 7% of the trainees reported these events to the graduate medical education office or program director.…”
Section: Discussionmentioning
confidence: 99%
“…While findings of high rates of microaggressions by specialty were found in surgery and surgical subspecialties (82.3%), followed by medical (30.1%) and dentistry (12.9%), these findings were consistent with reports from regions outside the Gulf/ME region. Microaggression and implicit bias in surgical training has been reported, in an American study by Alimi Yewande et al, in a national survey with a majority (72.2%, n = 1173) of respondents reported experiencing microaggressions, most commonly from patients (64.1%), followed by staff (57.5%), faculty (45.3%), and co-residents (38.8%), while only a small proportion ( n = 109, 7.0%) of residents reported these events to the graduate medical education office/program director, and nearly one-third (30.8%) of residents said they experienced retaliation after reporting a microaggression ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microaggressions occur in medicine and healthcare as reported in the literature ( 11 20 ), and they have been mentioned as one of the factors that negatively impact the workplace environment and medical education in different regions of the world ( 16 18 ). There is expanding literature on the prevalence of microaggressions in the healthcare setting.…”
Section: Introductionmentioning
confidence: 99%
“…Existing efforts to expand and support implicit bias training have become a priority for physician residencies over the course of their training [14][15][16][17][18][19][20][21][22][23][24] It should be noted that there is ample research indicating that PAs and NPs provide excellent clinical care without postgraduate residency/fellowship training [25,26]; nevertheless, there has been an expanded interest in these postgraduate programs from both federal and public sectors due in part to projected shortfalls in physician specialties and a desire among some PAs and NPs to improve "clinical readiness" through transition-to-practice opportunities. Additionally, some academic health systems have adopted PA and joint PA/NP fellowship/residency training programs to bolster recruitment and retention strategies of qualified career staff [27].…”
Section: Introductionmentioning
confidence: 99%